Comparison of Lignocaine and Fentanyl for Attenuation of Cardiovascular Stress Response to Laryngoscopy and Endotracheal Intubation (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUND AND AIM Intravenous Fentanyl Citrate and Lignocaine hydrochloride is being used as premedication for general anaesthesia with an intent to attenuate cardiovascular reflexes of laryngoscopy and endotracheal intubation. Present study was aimed to compare efficacy of both drugs as premedication to attenuate cardiovascular reflexes of laryngoscopy. METHODOLOGY Present study was carried out on randomly selected 50 patients of ASA Grade 1 and 2, aged 20 to 50 years with mallam pati airway assessment grade 1 scheduled for elective surgery requiring general anaesthesia with endotracheal intubation. All routine non-invasive monitors were applied and iv line secured. Glycopyrrolate 0.004 mg/kg and injection midazolam 0.02 mg/kg was given intravenously and IV infusion of ringer lactate was started. Patients were divided in two groups. Group-1: -Lignocaine hydrochloride group. Here patients received injection lignocaine hydrochloride 1.5 mg / kg IV bolus 3 minutes prior to induction. Group-2: -Fentanyl citrate group. Here patients received injection fentanyl citrate 2 µg / kg IV bolus 3 minutes prior to induction. After preoxygenation general anaesthesia with Thiopentone Sodium 5mg/kg and Succinyl choline 2mg/kg was given and endotracheal intubation was done. Heart rate, SBP, DBP, MAP and ECG were recorded in all patients pre operatively, after premedication, before study drug, after induction, after laryngoscopy and intubation and for every 1 minute up to 6 minutes after intubation during which no stimulus was given to patients. Laryngoscopy done and endotracheal intubation was done. An observation was made related to adverse effects of drugs and laryngoscopy related problems and were attended to appropriately. RESULTS In our study, injection fentanyl citrate 2 µg/kg attenuated the haemodynamic response better than Lignocaine 1.5 mg/kg. Heart rate, systolic blood pressure, diastolic blood presuure and mean arterial pressure did not rise significantly after intubation with Fentanyl compared to Lignocaine and reached basal value within study time. CONCLUSION Fentanyl citrate is safe and effective in attenuation of hemodynamic response to laryngoscopy without significant side effects as compared to lignocaine hydrochloride.
Keywords: LIGNOCAINE; FENTANYL; ATTENUATION; CARDIOVASCULAR